Extraction of oil and gas in Guzulshchyna at the second half of XIX - the first third of XX centuries - Volodymyr Klapchuk (Cхід, 2013)
The first oil well was planted in1771 inSloboda Rungurska (100 kgoil). Powerful development of oil production began in1865. Adeep drilling by steam engines was started in 1881. 50 oil wells were drilled in 1881, about 300 - in 1885. Oil transportation to the refiners since 1886 was carried out by three railways (32 km). One of the largest oil processing plants in Austria-Hungary was established in Pechenizhyn. 9870 tons of oil were produced in Sloboda Rungurska in 1893.